An Industrial quality control study on IDS Logistics (Involving Unilever Food Solutions Products) - Guarin, Andrei; Jalao, Eugene Rex; Quizon, Janine Lei; Ulpindo, Christopher Ian (College of Engineering, 2006)
In order to apply the statistical process control methods learned in IE 135, the group undertook a study on a company with certain methods and processes that needed to be monitored. Unilever Foods (formerly known as California Manufacturing Company or CMC), an already-established company in the Philippines, was chosen as the site, and the group was assigned to wkr specifically on the product lines of Best Foods Say Cheez and Lady's Choice Mayonnaise. These products are manufactured in Unilever's main plant located in Gateway Industrial Park in General Trias, Cavite, and thus the company relies on Integrated Distribution Systems (IDS) Logistics for its transportation and warehousing needs. In order to monitor the transportation of goos from plant to warehouse, both Unilever and IDS use what are called Stock Transfer Documents (STDs) and Short-Overlanded Advices (SOAs). The STDs contain information regarding the quantity as well as the descriptions of the products to be delivered (i.e. Best Before/BB dates and pallet number). the SOAs on the other hand, are used when products that are delivered and inspected either a) Do not match the description in the documents or b) are damaged and are damaged and therefore not counted as delivered in good condition. Upon the arrival of the goods in the Libis warehouse, IDS personnel perform 100 percent inspection on each pallet delivered. SOAs are then filled up and forwarded to the office where these forms are then documented. The data collected from seventeen weeks of deliveries (from May to September of 2005) were used by the group in order to analyze the reception process of IDS. IDS personnel classify problems with deliveries and indicate these in the SOAs according to these categories: A. Damaged Cartons B. Collapsed/Crushed Cartons C. Wet Cartons D. Product Leakages E. Oil Sep (mayo) F. Wrong BB. Dates G. No Labels in pallets/cartons. The group chose to utilize the P attributes control chart, since no measurement is involved in inspecting the products; these are only observed as in good condition (conforming) and damaged or with discrepancies (non-conforming).